IMPLEMENTASI ELEMEN EDITING PADA PRODUKSI FILM ANIMASI UNTUK MEMPERTAHANKAN KESINAMBUNGAN IMAJINASI PENONTON - Sarwanto, Sarwanto (Jurnal Ilmiah Multimedia dan Komunikasi, 2018)
Several cases of the production of animated films of Yogyakarta Multi Media High School students paid little attention to some elements of editing, so that the movement of images in the film often caused discomfort in the viewers. This discomfort can interfere with the continuity of the audience’s concentration. The disturbed concentration in the middle of the journey, resulting in the continuation of the imagination’s appreciation of the story being disrupted and even cut off. The research technique used is a qualitative descriptive approach, with the aim of describing objectively and systematically the extent to which the application of editing elements in animated film production is able to maintain the continuity of the audience’s imagination in understanding the meaning of the film. The research process was carried out by playing two types of animated films by students of the Animation Study Program in the presence of several viewers as respondents. Data analysis techniques are carried out by examining several images or shots from one image to another. The move is analyzed based on the editing element, the extent to which the editing element is applied. From the research process carried out, it was concluded that an animated film that applied the elements of editing, was easier to understand and remembered the whole storyline. So it is possible that information that is inserted through the film can reach the audience.